Modifications to the Current List of Financial Soundness Indicators. (Policy Papers; Policy Paper, 2013)
The purpose of this paper is to inform Executive Directors on the outcomes of consultations conducted by the IMF's Statistics Department (STA) on revising the current list of FSIs in response to the global financial crisis and the adoption of a new regulatory framework under the Basel III Accord. In addition, the G-20 Data Gaps Initiative calls on the IMF to review the FSI list (Recommendation numbers 2). STA has undertaken these consultations in close collaboration with a broad-based group of national and international experts, international standard setting bodies, IMF's relevant departments and all FSI-reporting countries and concerned international organizations.